EFFECTS OF MICROFINANCE SERVICES ON THE FINANCIAL PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN MOGADISHU, SOMALIA - MOHAMED, MOHAMUD AHMED; Mukhongo, Aaron L (IJRDO - Journal of Business Management, 2016)
In this study titled the effect of microfinance services on the financialperformance of small and medium enterprises, a case study of microfinanceinstitutions in Mogadishu, Somalia. Most of the small and medium enterprises inSomalia fail in their premature state, because of lack of insufficient capital, lack ofrisk awareness and the absence of financial literacy. The major objective of this studywas to measure the relationship between these above variables, the independent anddependent respectively. The specific objectives for this study include ascertaininghow financial sustainability affects financial performance in small and mediumenterprises in Mogadishu. The findings about this study stated that financialsustainability, financial literacy and risk diversification have moderate positiverelationship with financial performance of microfinance institutions in Mogadishu.The target population for this study consisted of four microfinance institutions SalamSomali Bank, Dahabshiil, Trust African bank and Kaah microfinance enterprise.Sample of 82 respondents was taken. The sample was chosen by using Slovene’sformula. Sampling technique for this study was non-random sampling particularlypurposive sampling. Descriptive research design was employed. Structuredquestionnaire have been designed to facilitate the acquisition of relevant data whichwas used for analysis. Descriptive statistics which involves simple tables andillustrations was tactically applied in data presentations and analysis. Regressionmodel was used to measure the kind of relationship that exists between theindependent and the dependent variable. The results of the study showed thatmoderate positive relationship exists between financial sustainability, financialliteracy, risk diversification and financial performance of microfinance institutions inMogadishu, Somalia. The researcher would like to recommend for the microfinanceinstitutions to expand their services to other parts of the country to distribute theopportunities that can be benefited by the poor citizens in entire the country